2022
DOI: 10.1111/jar.12992
|View full text |Cite
|
Sign up to set email alerts
|

Employment preferences of individuals with intellectual and developmental disabilities: An evaluation of gender and age differences

Abstract: Background Employment is often central to individuals' lives. However, individuals with intellectual or developmental disabilities are often absent from the workplace, and little research has examined their interest in working. Aims This study examined whether people with intellectual and/or developmental disabilities want jobs; why they do or do not want jobs; and, if they want to work, what types of jobs they would like to have. Materials and Methods Our analyses consisted of 629 participants (379 male, 248 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Research has demonstrated that individuals with intellectual disabilities do have an interest in employment with a significant number of people wanting to work (Hennessey & Goreczny, 2022). The Engage to Change project offered a wide variety of jobs to young people aged 16–25, from a large variety of sectors and businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that individuals with intellectual disabilities do have an interest in employment with a significant number of people wanting to work (Hennessey & Goreczny, 2022). The Engage to Change project offered a wide variety of jobs to young people aged 16–25, from a large variety of sectors and businesses.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, people with intellectual disabilities are the most vulnerable groups in employment (Karhina et al, 2022). Nevertheless, the particular group have a strong desire to earn a living (Hennessey & Goreczny, 2022;Stephens et al, 2005). They also have equal rights to work.…”
Section: Introductionmentioning
confidence: 99%
“…People with intellectual disabilities are the most disadvantaged group among all disability types when it comes to employment (Karhina et al, 2022).But it doesn't mean they don't have the right to work. Having a paid job is not only a strong personal desire for people with intellectual disabilities (Hennessey & Goreczny, 2022), but also is beneficial to the society and economy in the long run (Ellenkamp et al, 2016). Secondary vocational students with intellectual disabilities are important candidates for employees with intellectual disabilities because they are more likely to become good employees through vocational education and specialized training.…”
Section: Introductionmentioning
confidence: 99%